STUDENTS’ MATHEMATICS LEARNING OUTCOMES THROUGH ONLINE LEARNING - Fitriani Nur (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
The paradigm of online learning is an alternative at every level of education today. This study aims to describe students' math learning outcomes through online learning. The study involving all 1st graders of Madrasah Ibtidaiyah Madani Alauddin as many as 47 people used observation sheet instruments and documentation of learning results and analyzed using descriptive statistics. The results of this study showed that the average math learning outcomes of students are in the excellent category through online learning. Another finding from this study is that there are still 11% of students who need guidance on mathematics learning, so that further research can explore factors that hinder the understanding of student math learning today.